Parametric analysis of railway infrastructure for improved performance and lower life-cycle costs using machine learning techniques. (January 2023) - Sainz-Aja, Jose A.; Ferreño, Diego; Pombo, Joao; Carrascal, Isidro A.; Casado, Jose; Diego, Soraya; Castro, Jorge
Highlights: A parametric model of the whole railway track was developed. The parametric analysis combines finite element and machine learning algorithms. The importance of each variable on the response of the railway track was evaluated. The dependency of each variable on the track behaviour was estimated. Rail pad is the most important component in track's vertical stiffness. Abstract: Rigorous and efficient management of the railway infrastructure is crucial to avoid accidents and reduce operation and maintenance costs. This requires in-depth knowledge of the assets, the interaction among them and the effect that each track parameter has on the overall infrastructure performance. In this study, a large set of studies are carried out, on a previously calibrated finite element slab track model, where the relevant track parameters are varied within their usual ranges. The results are then used to train and validate a series of predictive models based on Machine Learning algorithms. This methodology provides greater understanding and enhanced prediction of the behaviour of tracks, which are composed of multiple variables such as the soil/subgrade, supporting layers, sleepers, pads and rails. The study also considers train axle loads and service speeds, which are other key elements that influence the track performance. The results show that the parameters that have greatest influence on the railway infrastructure are the properties of the soil, characteristics of the rail pads and the axle loads. This work can support the implementation of predictive maintenance procedures for railway tracks and the development of innovative technological solutions, providing responses to the industrial needs of reducing costs and contributing to improve the competitiveness of railway transport.